Properties of particleboard from Acacia Mangium (Mature) - Husin, Asma; Lias, Hazwani; Mohd Yasin, Nur Faizura; Mohd Yasin, Nurfazurain (2010)
In this study, three percentage of urea formaldehyde (UF) that are 8%, 10% and 12% will be mixed with the particle size that are 0.5mm, 1.0mm and 2.0mm. This mixed will be made a board called particleboard after been cured by heat and pressure. The properties of that particleboard will be determined by several types of test such as bending test, internal bonding, water absorption and thickness swelling. The result shows that the percentages of resin content, wax and particle size are affecting the properties of the board. For the standard of evaluating that particleboard reach the value that been specified. This particleboard is suitable as a raw material in wood base product.